A model‐based estimate of nitrate leaching in Germany for GHG reporting. Issue 6 (19th September 2022) - Eysholdt, Max; Kunkel, Ralf; Rösemann, Claus; Wendland, Frank; Wolters, Tim; Zinnbauer, Maximilian; Fuß, Roland
Abstract: Background: Conversion of leached and runoff nitrate (NO3 – ) from agricultural land into emissions of the greenhouse gas (GHG) nitrous oxide (N2 O) by denitrification in water bodies has to be reported in national GHG inventories. The global IPCC default methodology for estimating these indirect N2 O emissions assumes that a fixed fraction of nitrogen (N) inputs (Fracleach ) is lost through leaching and runoff. However, this method does not consider all relevant country‐specific conditions that may influence NO3 – leaching. Aims: The aim of this study was to apply a model‐based approach for estimating indirect N2 O emissions through NO3 – leaching and runoff from agricultural soils for use in Germany's national GHG inventory. Methods: High‐resolution spatial data and a comprehensive model system (RAUMIS‐mGROWA‐DENUZ) were used to derive regionally differentiated and temporarily dynamic Fracleach values from N surplus and hydrogeological conditions. These were then used to estimate indirect N2 O emissions in accordance with the IPCC methodology. Results: The nationwide average of the new implied Fracleach values was 0.099 kg N (kg N input) −1 in 2019. The new estimate of indirect N2 O emissions was 10.4 Gg N2 O in 1990 and 5.7 Gg N2 O in 2019, which are 27 and 52% less than the calculation based on the 2006 IPCC Tier 1 methodology. Conclusions: The model‐based method for estimating Fracleach incorporates relevant factors that influence NO3 – leaching and runoff and considers site‐specific, spatially varying conditions and differences in the agrarian structure. The use of N surplus as the model driver allows annual changes in cropping conditions and the effects of N‐regulating policies and mitigation measures to be represented.